Best Answer


15x - 20y = -1

15y = 2 + 5x


15x -20(2 + 5x)/15 = -1

∴15x -40/15 - 100x/15 = -15/15

∴225x/15 - 100x/15 = 40/15 - 15/15

∴125x = 25

∴x = 1/5


15(1/5) - 20(1/5) = -1

∴3 - 4 = -1

∴-1 = -1

User Avatar

Wiki User

โˆ™ 2009-07-27 22:53:34
This answer is:
User Avatar
Study guides


20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

See all cards
1770 Reviews

Add your answer:

Earn +20 pts
Q: Solve by the substitution method 15x-20y equals -1 15y equals 2 plus 5x?
Write your answer...
Still have questions?
magnify glass
Related questions

Solve the equation by substitution method x-y equals 5?


Use the substitution method to solve the system of equations Choose the correct ordered pair 2x plus 3y equals 13 x equals 2?


How can you solve a linear equation?

by elimination,substitution or through the matrix method.

Use the substitution method to solve the system of equations Enter your answer as an ordered pair?

Use the substitution method to solve the system of equations. Enter your answer as an ordered pair.y = 2x + 5 x = 1

Can quadratic systems be solved using elimination and substitution?

You can solve lineaar quadratic systems by either the elimination or the substitution methods. You can also solve them using the comparison method. Which method works best depends on which method the person solving them is comfortable with.

how to solve simultaneous equation?

It has two methods. One is substitution method, and second one is elimination method

When solving by the substitution method what happens when one variable cancels out?

That's exactly the purpose of the substitution method ... to get an equation with one less variable. When you have it, you solve it for the variable that's left.

How do you solve x plus y equals 4 and y equals 2X plus 1 by substitution method?

If: x+y = 4 and y = 2x+1 Then: 4-x = 2x+1 => 3 = 3x => 1 = x So by substitution: x = 1 and y = 3

Solve by substitution method y equals -4x - 7 y equals 3x?

y= -4x-7 y=3x 3x= -4x-7 3x+4x=7 7x=7 x=1

How do you solve a problem using the substitution method?

You solve this by theoretically diverting the hypotenuse of the x divided by the overall beneficial procedure of y

What 4x y14 and 2x y8 solve using substitution?

You cant solve it unless it is an equation. To be an equation it must have an equals sign.

Solve using substitution x minus y equals 2 and x plus y equals -4?


People also asked